2021
DOI: 10.1038/s41370-021-00291-y
|View full text |Cite
|
Sign up to set email alerts
|

Daily mean temperature and HFMD: risk assessment and attributable fraction identification in Ningbo China

Abstract: Background Hand, foot, and mouth disease (HFMD) remains a significant public health issue, especially in developing countries. Many studies have reported the association between environmental temperature and HFMD. However, the results are highly heterogeneous in different regions. In addition, there are few studies on the attributable risk of HFMD due to temperature. Objectives The study aimed to assess the association between temperature and HFMD incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Meteorological factors could affect the incidence of HFMD by influencing the breeding, growth, and transmission of pathogens, as well as human behaviors [ 29 , 30 , 31 ]. Many previous studies have shed light on the non-linear effects of meteorological factors on HFMD [ 32 , 33 , 34 , 35 ]. According to the principle of the neural network model, LSTM can effectively fit these non-linear meteorological data.…”
Section: Discussionmentioning
confidence: 99%
“…Meteorological factors could affect the incidence of HFMD by influencing the breeding, growth, and transmission of pathogens, as well as human behaviors [ 29 , 30 , 31 ]. Many previous studies have shed light on the non-linear effects of meteorological factors on HFMD [ 32 , 33 , 34 , 35 ]. According to the principle of the neural network model, LSTM can effectively fit these non-linear meteorological data.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison of the attributable fractions of air pollutants revealed that the health effects of O 3 were much greater than those of other air pollutants, particularly in basin and mountain regions. In previous studies, temperature and relative humidity, the two most popular environmental factors, were commonly identified to have significant impacts on HFMD risks [ 33 , 54 , 55 ]. The attributable fractions of high temperature and relative humidity in previous studies reached 39.55% [ 54 ] and 14.56% [ 33 ], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, temperature and relative humidity, the two most popular environmental factors, were commonly identified to have significant impacts on HFMD risks [ 33 , 54 , 55 ]. The attributable fractions of high temperature and relative humidity in previous studies reached 39.55% [ 54 ] and 14.56% [ 33 ], respectively. The latter was relatively close to the AFs for the high levels of PM 10 (13.38%) and O 3 (16.83%) that were calculated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Ambient heat exposure was suggested to be one of the most important environmental factors that were associated with an elevated risk of HFMD in numerous previous studies [ 10 , 11 ]. For example, a systematic review on top of 11 studies previously conducted in Asia-Pacific regions suggested an average 5(2–8)% increase in the incidence of HFMD per 1°C increase in the temperature [ 12 ].…”
Section: Introductionmentioning
confidence: 99%